The effects of staged mixing on the dispersion of reinforcing fillers in elastomer compounds. (24th October 2019) - McGlasson, Alex; Rishi, Kabir; Beaucage, Gregory; Narayanan, Vishak; Chauby, Michael; Mulderig, Andrew; Kuppa, Vikram K.; Ilavsky, Jan; Rackaitis, Mindaugas
Abstract: Kinetically mixed reinforcing fillers are dispersed by accumulated strain. Processing conditions such as mixing geometry, intensity and the duration of mixing are key elements that control accumulated strain. A simple method to modify mechanical mixing is the mixing schedule which involves the timing of filler additions to a compound. For example, it is known that simultaneous addition of oil with filler is disadvantageous to dispersion, while the incorporation of oil after filler addition enhances dispersion. The simplest case of mixing schedule involves timed filler additions into an elastomer, for instance in a single stage or in two-stages. This study explores the effects of staged mixing on nanoscale dispersion based on a colloidal model. Dispersion is quantified using a pseudo-thermodynamic approach coupled with ultra-small angle X-ray scattering. It was found that single stage mixing yields optimal nano-dispersion for carbon-coated silica and carbon black in polybutadiene using an internal mixer. Graphical abstract: Image 1 Highlights: Nano-scale dispersion of filler quantified by small-angle X-ray scattering. Colloidal analogy relates thermal motion to kinetic dispersion via accumulated strain. Filler interactions modelled by two parameters from the van der Waals equation. Aggregate excluded volume related to the hard-sphere aggregate volume. Aggregate interaction energy depends on the extent of carbon coverage on the silica surface.